Pattern of FDG-PET uptake in lipoid pneumonia simulating lung cancer. (2020) - Nakagawara, Kensuke; Sasaki, Mamoru; Morinaga, Shojiroh; Minematsu, Naoto
Abstract: Lipoid pneumonia presents with a variety of lung abnormalities, particularly mass forming lesions that mimic lung cancers. While 18 F-fluorodeoxyglucose (FDG)-positron emission tomography (PET) is expected to discriminate both diseases, some previous reports showed pseudo-positive FDG uptake in lipoid pneumonia. Here, we report a case of pathologically proven chronic lipoid pneumonia in a 78-year-old Japanese man. Computed tomography (CT) showed multi-lobar mass-forming lesions with a fat-density. PET confirmed the spotty accumulation of FDG in the corresponding fat-density area on CT, suggesting lipoid pneumonia. We reviewed the literature and discussed the FDG uptake patterns in lipoid pneumonia.